(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
Phase change in ice-water systems in the geometry of horizontal cylindrical annulus with constant inner wall temperature and adiabatic outer wall is modeled with an enthalpy-based mixture model. Solidification and melting phenomena under different temperature conditions are analyzed through a sequence of numerical calculations. In the case of freezing of water, the importance of convection and conduction as well as the influence of cold pipe temperature on time for the complete solidification is examined. As for the case of melting of ice, the influence of the inner pipe wall temperature on the shape of the ice-water interface, the flow and temperature fields in the liquid, the heat transfer coefficients and the rate of melting are analyzed. The results of numerical calculations point to good qualitative agreement with the available experimental and other numerical results.